Growth and Extracelluler Polysaccaride Production of Porphyridium cruentum In Various Photoperiod - Himawan Prasetyo; Iriani Setyaningsih; Dewi Ratih Agungpriyono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Porphyridium cruentum is a kind of red microalgae (Rhodophyta) that can grow and producepolysaccharides. Polysaccharides are produced on the cell, then released and accumulated byextracellular into medias. This study aimed to determine the optimum growth and productionof extracellular polysaccharides (EPs) from P. cruentum in various photoperiods. The cultivationwas done with the photoperiods at 24:0, 18:6, 12:12 and 06:18 h (light:dark) during 40 days usingmodified medium F/2. The growth is determined by measuring optical density (OD) and driedbiomasses, the productions of EPs are determined by dried weight polysaccharides as a resultof precipitation. The results showed that OD at photoperiod 24:0 has the highest value 0.876 ±0.0645 unit of absorbance, biomass concentrations are highest in the photoperiod 24:0 and 12:12respectively 716.12 ± 123 mg-l and 696.5 ± 74.5 mg-l, the highest production of EPs on thephotoperiod 12:12 is 1.310 ± 130.26 mg-l. 12:12 hours (light: dark) photoperiod is optimally usedin P. cruentum cultivations with high biomass and extracellular polysaccharide results.